PENGARUH DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE DI PERUSAHAAN PERBANKAN - Rini Handayani (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2017)
Currently, the government seeks to address high tax avoidance rates by improving the quality of corporate governance (GCG), and applying Corporate Social Responsibility that is part of Good Corporate Governance. The purpose of this research is to know the influence of Independent Board of Commissioner, Institutional Ownership which is part of Good Corporate Governance and Corporate Social Responsibility to Corporate Banking Tax Avoidance. This research is included in the research type of explanatory document creation strategy. The object of this study is a Banking Company listed on the Stock Exchange in 2012-2015. The number of samples in this study as many as 50 banks in accordance with the criteria. The analysis method used is descriptive statistical analysis and multiple linear regression. Based on the results, in part, there is no influence between the indicator of Institutional Ownership and the Board of Commissioners regarding Tax Avoidance. While Corporate Social Responsibility has a partial effect on Tax Avoidance. While simultaneously there is influence of Independent Board of Commissioners, Institutional Ownership and Corporate Social Responsibility to Avoidance Pajaksebesar 65%.